Islamic Boarding Schools as the Basis of Educational Institutions and Life Skill Development - Helmi, Helmi (Ruhama : Islamic Education Journal, 2023)
Competition in the era of globalization requires human resources who have skills, otherwise the existing human resources are automatically faced with the difficulty of getting a job to make ends meet. In line with that, educational institutions do not always have programmes that lead to the development of skills for students. Therefore, this study aims to find the forms of life skills development programmed by Islamic boarding schools. This research was conducted using qualitative methods, interviews, observations and documentation studies were used as data collection techniques. From the data found, it can be stated that Islamic boarding schools as educational institutions have several programmes in developing students' life skills, namely skills as preachers, skills as imams, skills in communication, resilience, cooperation, problem solving, and empathy. Some of these life skills can be developed in Islamic boarding schools because they are in line with the established curriculum.